Letter from T B S Macaulay to Thomas Hickey - Macaulay, T. B. S.; Anti-Partition League, AL (1938)
Manuscript letter dated 27 November 1938, to ask the addressee to cover the Exhibition of Art at Bethnal Green Museum with the "English Press".